Evaluation of International Reference Ionosphere 2000 at a midlatitude station - Mansilla, Gustavo Adolfo (2007)
To check the validity of the latest version of the International Reference Ionosphere (IRI-2000) which contains geomagnetic activity dependence based on an empirical storm-time ionospheric correction (STORM model), comparison of measured foF2 values with those obtained from the model was made. To quantify the degree of accuracy of the IRI-2000 model during disturbed conditions the relative difference between the model outputs (with STORM model turned on and turned off options) and experimental data was calculated. The ionosonde foF2 data used were obtained at Ebro Observatory (40.80 N; 0.490 E; geomagnetic latitude = 43.20 N) during intense geomagnetic storms occurring in the years 2000 and 2001 (high solar activity). Although only a few case studies comparisons have been made the results show that during storm conditions predicted values with the STORM model included in IRI-2000 follow the variations of foF2 data better than IRI-2000 without the STORM model. In general IRI-2000 with the STORM model has almost 30 – 40 % improvement over IRI-2000 without the STORM model. The greater deviations between model outputs and observations are observed during the end of the main phase and early stage of the recovery phase. For this station, in general IRI predictions with the STORM model underestimate foF2 data in February-March and significantly overestimate in April-May